UJI EFEK SEDATIF INFUSA DAUN KRATOM (Mitragyna speciosa) PADA MENCIT JANTAN GALUR BALB/c - ., Dini Novindriani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran dan Ilmu Kesehatan UNTAN, 2013)
Insomnia  is a condition difficult start to sleep, can not sleep or inadequate sleepduration. One of plants which guess have sedative effect is kratom (Mitragyna speciosa). This research was conducted to determine the sedative effect of kratom leaves infusa to male BALB/cstrain mice. In addition, it aims to determine the effective dose and potential kratom leaves infusawhen compared with diazepam The mice divided into 5 groups of  positive control group (diazepam), negative control(aquadest), and infusa of kratom leaves groups dose 1,95; 3,9; and 7,8 g/KgBW. The test of sedativeeffect was conducted with Traction test and Fireplace test method on male BALB/c strain mice.Monitoring of quantitative data are duration time of mice to turning the body and duration time ofmice to fall down, as soon as duration time of mice to come out from cylinder tube. Qualitative data isobserved presence or absence of reflexes behind the body and corneal reflexes. Result of the quantitative data was analyzed with One Way ANOVA and supported by SPSS.Based on the result, all of kratom leaves infusa dosages has sedative effect, which is the mosteffective dose kratom leaves infusa at dose of 7.80 g / KgBW. But  the sedative effect still below ofdiazepam. Key Word : kratom leaves, sedatives, infusa.